Drug-Induced Acute Pancreatitis in a Cohort of 328 Patients. A Single-Centre Experience from Australia - Barreto, Savio George; Tiong, Leong; Williams, Randall (JOP. Journal of the Pancreas, 2011)
<!–[if gte mso 9]> Normal 0 14 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Context Acute pancreatitis is associated with risk of morbidity and even mortality. Routine prescription drugs have been linked to the causation of acute pancreatitis. Objective To determine the incidence, presentation, course and outcome of drug-induced acute pancreatitis amongst patients admitted to a public hospital. Design/setting A retrospective analysis of patients presenting with acute pancreatitis to the Modbury Hospital, South Australia from January 2006 to April 2011. Main outcome measure Each admission was reviewed within the electronic database for patient details as well as to determine the aetiological factor. In patients with drug-induced acute pancreatitis, the WHO Probability Scale was used to evaluate causality relationship. Results Three-hundreds and 28 patients were treated for acute pancreatitis during the study period. Biliary and alcohol-induced acute pancreatitis accounted for 80.8% of cases. Eleven patients (2 male and 9 female patients; median age: 59 years) were diagnosed with drug-induced acute pancreatitis. These included 5 cases of codeine-, 2 cases of azathioprine-, and 1 case each of chlorothiazide-, valproic acid-, oestradiol- and rosuvastatin-induced acute pancreatitis. Nine patients had a mild disease while 2 patients had severe acute pancreatitis with a median hospital stay of 4 days. Withdrawal of the drug resulted in cessation of the attacks in all patients over a median follow-up of 24 months. Conclusions Routine prescription drugs, as an aetiological factor, accounted for 3.4% of cases of acute pancreatitis. The disease appeared to be more common in middle-aged women. It is likely that the overall incidence of this entity is under-reported owing to the stringent criteria needed to conclusively determine a causal relationship.